Dental Caries and Enamelin Haplotype. (April 2014) - Chaussain, C.; Bouazza, N.; Gasse, B.; Laffont, A.G.; Opsahl Vital, S.; Davit-Béal, T.; Moulis, E.; Chabadel, O.; Hennequin, M.; Courson, F.; Droz, D.; Vaysse, F.; et al.
In the literature, the enamelin gene ENAM has been repeatedly designated as a possible candidate for caries susceptibility. Here, we checked whether ENAM variants could increase caries susceptibility. To this aim, we sequenced coding exons and exon-intron boundaries of ENAM in 250 children with a severe caries phenotype and in 149 caries-free patients from 9 French hospital groups. In total, 23 single-nucleotide polymorphisms (SNPs) were found, but none appeared to be responsible for a direct change of ENAM function. Six SNPs had a high minor allele frequency (MAF) and 6 others were identified for the first time. Statistical and evolutionary analyses showed that none of these SNPs was associated with caries susceptibility or caries protection when studied separately and challenged with environmental factors. However, haplotype interaction analysis showed that the presence, in a same variant, of 2 exonic SNPs (rs7671281 and rs3796704; MAF 0.12 and 0.10, respectively), both changing an amino acid in the protein region encoded by exon 10 (p.I648T and p.R763Q, respectively), increased caries susceptibility 2.66-fold independent of the environmental risk factors. These findings support ENAM as a gene candidate for caries susceptibility in the studied population.